Small Molecule Inhibiting Nuclear Factor‐kB Ameliorates Oxidative Stress and Suppresses Renal Inflammation in Early Stage of Alloxan‐Induced Diabetic Nephropathy in Rat. Issue 5 (23rd January 2017) - Borgohain, Manash P.; Lahkar, Mangala; Ahmed, Sahabuddin; Chowdhury, Liakat; Kumar, Saurabh; Pant, Rajat; Choubey, Abhinav
Abstract: Diabetic nephropathy is one of the major microvascular complications of diabetes mellitus which ultimately gives rise to cardiovascular diseases. Prolonged hyperglycaemia and chronic renal inflammation are the two key players in the development and progression of diabetic nephropathy. Nuclear factor kB (NF‐kB)‐mediated inflammatory cascade is a strong contributor to the renovascular inflammation in diabetic nephropathy. Here, we studied the effects of piceatannol, a potent NF‐kB inhibitor, on various oxidative stress markers and NF‐kB dependent diabetic renoinflammatory cascades in rat induced by alloxan (ALX). Experimental diabetes was induced in male Wistar rats by a single intraperitoneal dose, 150 mg/kg body‐weight (b.w.) of ALX. Diabetic rats were treated with Piceatannol (PCTNL) at a dose of 30 and 50 mg/kg b.w. After 14 days of oral treatment, PCTNL significantly restored blood sugar level, glomerular filtration rate, serum markers and plasma lipids. PCTNL administration also reversed the declined activity of cellular antioxidant machineries namely superoxide dismutase and glutathione and the elevated levels of malondialdehyde and nitric oxide. Moreover, piceatannol‐treated groups showed marked inhibition of renal pro‐inflammatory cytokines and NF‐kB p65/p50 binding to DNA. Renal histopathological investigations also supported its ameliorative effects against diabetic kidney damage. Importantly, effects were more prominent at a dose of 50 mg/kg, and in terms of body‐weight gain, PCTNL failed to effect significantly. However, overall findings clearly demonstrated that PCTNL provides remarkable renoprotection in diabetes by abrogating oxidative stress and NF‐kB activation – and might be helpful in early stage of diabetic nephropathy.